2017
DOI: 10.4103/2277-9175.201334
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Expression of DT386-BR2 Fusion Protein in Escherichia coli using Response Surface Methodology

Abstract: Background:The aim of this study was to determine the best condition for the production of DT386-BR2 fusion protein, an immunotoxin consisting of catalytic and translocation domains of diphtheria toxin fused to BR2, a cancer specific cell penetrating peptide, for targeted eradication of cancer cells, in terms of the host, cultivation condition, and culture medium.Materials and Methods:Recombinant pET28a vector containing the codons optimized for the expression of the DT386-BR2 gene was transformed to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
3
5
0
3
Order By: Relevance
“…The reason of inducing AluY RNA yield decreased maybe that RNA easily degrade. Shafiee et al [ 29 ] found that the IPTG concentration had the most effect on protein expression and the optimal IPTG concentration was 1 mmol/l; in this paper, we found that optimal IPTG concentration was 0.1–0.4 mg/ml (0.42–1.68 mmol/l) (Fig. 1 d).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The reason of inducing AluY RNA yield decreased maybe that RNA easily degrade. Shafiee et al [ 29 ] found that the IPTG concentration had the most effect on protein expression and the optimal IPTG concentration was 1 mmol/l; in this paper, we found that optimal IPTG concentration was 0.1–0.4 mg/ml (0.42–1.68 mmol/l) (Fig. 1 d).…”
Section: Discussionsupporting
confidence: 61%
“…Shafiee et al [ 29 ] showed the highest level of DT386-BR2 fusion protein expression was attained after 2 h of incubation with IPTG and increasing the incubation time did not affect the amount of expression; in this paper, we found that AluY RNA yield reached peak at 4 h of IPTG induction, remarkably decreased after 8 h with IPTG induction. The reason of inducing AluY RNA yield decreased maybe that RNA easily degrade.…”
Section: Discussionsupporting
confidence: 47%
“…Assim como verificado em outros trabalhos (ASHAYERI-PANAH et al 2017;SHAFIEE et al 2017) a melhor expressão ocorreu a 37 °C.…”
Section: Otimização De Parâmetros Na Produção De Eraunclassified
“…A concentração do indutor também afeta a expressão da proteína. A baixa concentração do indutor pode resultar em uma indução ineficiente e por outro lado, os indutores adicionados em excesso podem resultar em efeitos tóxicos, incluindo crescimento celular reduzido e, finalmente, redução da concentração de proteína recombinante (RAMIREZ et al 1994;SHAFIEE et al 2017). Nesse trabalho foi possível verificar que a concentração do indutor afetou os valores obtidos de atividade específica, principalmente no caso de temperaturas mais baixas.…”
Section: Otimização De Parâmetros Na Produção De Eraunclassified
See 1 more Smart Citation